Meta-evaluation of History and English Language Pedagogy Study Programme with Focus on Transformational Learning - Andziulienė, Loreta (Pedagogika, 2016)
Higher education internalization, professional mobility and competitive participation in the international labour market requires the new 21st century competences that involve the transformational change of future teachers, academic staff and the teacher training institution itself. Integrated content and foreign language (CLIL) study programmes create preconditions for such transformational learning based on cooperative learning/teaching, critical thinking, formative assessment and reflection. Simulations, case studies, problem solving, project work, research based learning develop students’ ability to work cooperatively and produce collectively. Pedagogical scaffolding strategies, constructive feedback and formative assessment enable students monitor their progress and plan their further learning. Systematic reflection helps understand better meaningfulness and complexity of the teaching profession, directs one’s transformation and equips students with lifelong learning skills. CLIL study programs prove to have high transformational impact on in-service teachers’ conceptual thinking, procedural skills and encourage reassessing the validity of learning. Ability to direct one’s change empowers future teachers to construct and reconstruct their knowledge based on their experience and needs, critically evaluate educational and work environment, transfer the acquired knowledge and skills to new contexts and actively participate in the reconstruction of the changing society.